2005
DOI: 10.1021/jp052904i
|View full text |Cite
|
Sign up to set email alerts
|

The Mesoscopic Dynamics of Thermodynamic Systems

Abstract: Concepts of everyday use such as energy, heat, and temperature have acquired a precise meaning after the development of thermodynamics. Thermodynamics provides the basis for understanding how heat and work are related and the general rules that the macroscopic properties of systems at equilibrium follow. Outside equilibrium and away from macroscopic regimes, most of those rules cannot be applied directly. Here we present recent developments that extend the applicability of thermodynamic concepts deep into meso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
296
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(305 citation statements)
references
References 70 publications
2
296
0
7
Order By: Relevance
“…͑13d͒ itself. In this respect we mention that, although this criticism may be valid, recent developments 17,18 have shown that by introducing an internal mesoscopic variable to describe the advancement of a chemical reaction, a linear phenomenological law similar to Eq. ͑13d͒ can be formulated in terms of that mesoscopic variable, thereby extending the validity of linear nonequilibrium thermodynamics ͑and its associated theory of fluctuating hydrodynamics, to be developed later in Sec.…”
Section: B Phenomenological Relationshipsmentioning
confidence: 99%
“…͑13d͒ itself. In this respect we mention that, although this criticism may be valid, recent developments 17,18 have shown that by introducing an internal mesoscopic variable to describe the advancement of a chemical reaction, a linear phenomenological law similar to Eq. ͑13d͒ can be formulated in terms of that mesoscopic variable, thereby extending the validity of linear nonequilibrium thermodynamics ͑and its associated theory of fluctuating hydrodynamics, to be developed later in Sec.…”
Section: B Phenomenological Relationshipsmentioning
confidence: 99%
“…The main assumption of the MFPT and MLT methods is that the dynamics of the reaction in terms of the reaction coordinate, n s , is described by the onedimensional Fokker-Planck equation 14 for the probability density function p(n s , t) of n s at time t:…”
Section: Resultsmentioning
confidence: 99%
“…The relaxation of the polarisation can also be studied in the framework of nonequilibrium thermodynamics [5,7]. The relaxation process is dissipative and therefore entails an entropy production.…”
Section: Non-markovian Dielectric Relaxationmentioning
confidence: 99%